Cold season soil NO fluxes from a temperate forest: drivers and contribution to annual budgets - Medinets, Sergiy; Gasche, Rainer; Skiba, Ute; Schindlbacher, A.; Kiese, Ralf; Butterbach-Bahl, Klaus (IOP Publishing, 2016)
Soils, and here specifically acidic forest soils exposed to high rates of atmospheric nitrogen deposition, are a significant source for the secondary greenhouse gas nitric oxide (NO). However, as flux estimates are mainly based on measurements during the vegetation period, annual NO emissions budgets may hold uncertainty as cold season soil NO fluxes have rarely been quantified. Here we analyzed cold season soil NO fluxes and potential environmental drivers on the basis of the most extensive database on forest soil NO fluxes obtained at the Höglwald Forest, Germany, spanning the years 1994 to 2010. On average, the cold season (daily average air temperature <3 °C) contributed to 22% of the annual soil NO budget, varying from 13% to 41% between individual cold seasons. Temperature was the main controlling factor of the cold season NO fluxes, whereas during freeze-thaw cycles soil moisture availability determined NO emission rates. The importance of cold season soil NO fluxes for annual NO fluxes depended positively on the length of the cold season, but responded negatively to frost events. Snow cover did not significantly affect cold season soil NO fluxes. Cold season NO fluxes significantly correlated with cold season soil carbon dioxide (CO2) emissions. During freeze-thaw periods strong positive correlations between NO and N2O fluxes were observed, though stimulation of NO fluxes by freeze-thaw was by far less pronounced as compared to N2O. Except for freeze-thaw periods NO fluxes significantly exceeded those for N2O during the cold season period. We conclude that in temperate forest ecosystems cold season NO emissions can contribute substantially to the annual NO budget and this contribution is significantly higher in years with long lasting but mild (less frost events) cold seasons.